Linguocultural interpretation of the concepts “hospitality” and “mehmondustlik” in the russian and uzbek linguistic worldviews - Ismatova, Durdona; Azizova, Nasiba Bakhritdinovna (The Lingua Spectrum, 2026)
The article analyzes the cultural concepts of hospitality and mehmondustlik based on materials from the Russian and Uzbek languages. Using a three-component structure (conceptual, figurative, and value components), the author identifies both universal and ethnospecific features of these concepts. The etymological analysis demonstrates that the Russian word gost’ (“guest”) originates from the meaning “stranger,” whereas the Uzbek word mehmon is associated with the meaning “one who honors the household.” The figurative component in Russian culture is shaped by the metaphors of bread and salt and the open home, while in Uzbek culture it is represented by the images of the dastarkhan and the guest as “God’s guest.” The value core in Russian linguoculture is associated with cordiality and social reputation, whereas in Uzbek culture it is linked to sacred duty and the attainment of baraka (divine blessing). A comparison of nonverbal rituals further confirms these differences. The findings may be applied in language teaching and the theory of intercultural communication.